Islamic education curriculum management at SMK Al-Ghazaly Bogor - Enung Nurjanah; Maemunah Sa’diyah; Ouedraogo Saidou (At Turots: Jurnal Pendidikan Islam, 2024)
This study aims to analyze the management of Islamic education curriculum at SMK Al-Ghazaly Bogor. Islamic religious education in the 2013 curriculum at both high school and vocational school levels is included in group A subjects that must be followed by students, as well as in the independent curriculum in accordance with the learning achievements of Islamic religious education at both high school and vocational school levels. The research method used is qualitative descriptive. Primary data sources were taken from the principal, curriculum and representatives of Islamic Education teachers. Secondary data sources were taken from the Qur'an, Hadith, journals and other books. The background that drives the research is that SMK Al-Ghazaly Bogor is an Islamic-based school that has a Vision of building independent people based on IMTAQ and IPTEK, having good morals, skilled, productive and useful for society. The mission of SMK Al-Ghazaly Bogor is to realize a superior school with Islamic characteristics, build independent people who are ready to work and improve students' abilities in utilizing science and technology. SMK Al-Ghazaly Bogor was established in 2009 with an operational permit from the Bogor City Education Office number: 421.5 / 8-1 Disdikpora is an integrated part of the secondary education system under the auspices of the Ministry of National Education and Culture, the Directorate General of Vocational High School Development and the Al-Ghazaly Bogor Islamic Center Foundation is a foundation founded by one of Indonesia's great scholars, namely KH.R. Abdullah bin Nuh, which is now led by his son, KH. M. Mustofa ABN, Lc. Research results: This school focuses on the learning process balanced with Islamic-nuanced education such as dhuha prayer, tahsin tahfiz, surau tahajud together, memorizing the Qur'an, congregational fadhu prayer and annisa arrijal activities in Islamic education, approaches to discipline, habituation activities and attention to all aspects that support the learning process. Among the curriculum management described in this article are planning, organizing, implementing, supervising and evaluating the Islamic education curriculum at SMK Al-Ghazaly Bogor.